ANALYSIS OF DRAINAGE CHANNEL CAPACITY AT SINDANG STREET IN SINDANG HOUSE PUMP AREA - Imamuddin, Mohammad; Cahyanto, Dwi (ASTONJADRO, 2020)
Sindang street, which is located in North Rawabadak Sub-district, Koja District, is one of the areas in North Jakarta Administrative City which is an area that is prone to flooding. Even though a working pump house is available, there are still puddles in several places. One of the problems that occur is the channel that drains water into the storage pool narrowing due to sedimentation in the channel. By analyzing the channel using the Log Pearson III distribution method using data obtained from the STA Tanjung Priok Rainfall Station, the rainfall intensity that occurs in a 5 year cycle is 170.748 mm, the Mononobe equation is used to find the intensity of rain per hour that occurs. Then it can be searched for the planned rain discharge using a Rational Method so that it is known that there are 2 channels, namely (P and Q) unable to accommodate the rainfall that occurs.